Pengaruh Prenatal Yoga terhadap Kualitas Tidur Ibu Hamil Trimester III di TPMB Hj. A. Nani Nurcahyani - Siti Husaema; Afriani Afriani; Maria Sonda; Agustina Ningsi; Sitti Mukarramah (Media Kesehatan Politeknik Kesehatan Makassar, 2024)
Sleep disturbances in third-trimester pregnant women are often caused by an enlarging abdomen, which can press on the diaphragm and interfere with breathing, making it difficult for the mother to sleep. Other contributing factors include increased fetal weight, shortness of breath, fetal movements, frequent awakenings due to the need to urinate, and back pain. Prenatal yoga aims to prepare pregnant women physically, regulate breathing, improve blood circulation throughout the body, and relax the pelvic and uterine muscles in preparation for labor. This study aims to determine the effectiveness of prenatal yoga on the sleep quality of third-trimester pregnant women. The type of research used is a pre-experiment with a one-group pretest-posttest design. The sampling technique used is purposive sampling, with a sample size of 34 pregnant women who are physically and mentally healthy. Data analysis was conducted using univariate analysis and the Wilcoxon test. The results showed a significant effectiveness (p=0.000 < 0.05), which proves that prenatal yoga has a positive effect on the sleep quality of third-trimester pregnant women at TPMB Hj. A. Nani Nurcahyani, S.ST. This study contributes to the literature on non-pharmacological interventions to improve the sleep quality of pregnant women and adds insight into the benefits of prenatal yoga in maternal care. Keywords: Sleep quality; Prenatal Yoga; Pregnant women